Sei sulla pagina 1di 12

## Instrucciones: Verique las siguientes identidades trigonométricas.

1. cos4 A − sen4 A + 1 = 2cos2 A

## cos4 A − sen4 A + 1 = (cos2 A + sen2 A) · (cos2 A − sen2 A) + 1

= 1 · (cos2 A − sen2 A) + 1
= cos2 A − (1 − cos2 A) + 1
= cos2 A − 1 + cos2 A + 1
= 2cos2 A 

## sen3 A + cos3 A = (senA + cosA)(sen2 A − senAcosA + cos2 A)

= (senA + cosA)(1 − senAcosA) 

senA 1 + cosA
3. + = 2cscA
1 + cosA senA
senA 1 + cosA senA 1 − cosA 1 + cosA
+ = · +
1 + cosA senA 1 + cosA 1 − cosA senA
senA(1 − cosA) 1 + cosA
= +
1 − cos2 A senA
senA(1 − cosA) 1 + cosA
= +
sen2 A senA
  − cosA)
senA(1 1 + cosA
= +
sen2 A senA
1 − cosA 1 + cosA
= +
senA senA
1 − cosA + 1 + cosA
=
senA
1 −cosA
 + 1 +  cosA

=
senA
2
=
senA
= 2cscA 

1
4. cos6 A + sen6 A = 1 − 3sen2 Acos2 A

## cos6 A + sen6 A = (cos2 A)3 + (sen2 A)3

= (cos2 A + sen2 A) · (cos4 A − cos2 Asen2 A + sen4 A)
= 1 · (cos4 A − cos2 Asen2 A + sen4 A)
= cos4 A + sen4 A − cos2 Asen2 A
= (cos2 A)2 + (sen2 A)2 − cos2 Asen2 A
= (cos2 A)2 + 2cos2 Asen2 A + (sen2 A)2 − cos2 Asen2 A − 2cos2 Asen2 A
= (cos2 A + sen2 A)2 − 3cos2 Asen2 A
= 12 − 3cos2 Asen2 A
= 1 − 3cos2 Asen2 A 
r
1 − senA
5. = secA − tanA
1 + senA
r r
1 − senA 1 − senA 1 − senA
= ·
1 + senA 1 + senA 1 − senA
r
(1 − senA)2
=
1 − sen2 A
r
(1 − senA)2
= 2
p cos A
(1 − senA)2
= √
cos2 A
|1 − senA|
=
|cosA|
1 − senA
= Si cosA > 0
|cosA|
1 − senA
=
cosA
1 senA
= −
cosA cosA
= secA − tanA 

2
cscA cscA
6. + = 2sec2 A
cscA − 1 cscA + 1
 
cscA cscA 1 1
+ = cscA +
cscA − 1 cscA + 1 cscA − 1 cscA + 1
 
cscA + 1 + cscA − 1
= cscA
(cscA − 1)(cscA + 1)
2cscA
= cscA 2
csc A − 1
2
2csc A
=
cot2 A
2
sen
 2
A
= 
2
cos A
sen
  2
A
2
=
cos2 A
= 2sec2 A 
cscA
7. = cosA
cotA + tanA
1
cscA senA
= cosA
cotA + tanA senA
+ senA
cosA
1
senA
= cos2 A+sen2 A
senAcosA
1
senA

= 
1
senAcosA
 
cosA
=
1
= cosA 

## (secA + cosA)(secA − cosA) = sec2 A − cos2 A

= 1 + tan2 A − (1 − sen2 A)
= 1 + tan2 A − 1 + sen2 A
= tan2 A + sen2 A 
1
9. = senAcosA
cotA + tanA
1 1
= cosA senA
cotA + tanA senA
+ cosA
1
= cos2 A+sen2 A
senAcosA
1
= 1
senAcosA
= senAcosA 

3
1
10. = secA + tanA
secA − tanA
1 1 secA + tanA
= ·
secA − tanA secA − tanA secA + tanA
secA + tanA
=
sec2 A − tan2 A
secA + tanA
=
1
= secA + tanA 

1 − tanA cotA − 1
11. =
1 + tanA cotA + 1
1 − tanA 1 − tanA cotA
= ·
1 + tanA 1 + tanA cotA
cotA − 1
= 
cotA + 1

1 + tan2 A sen2 A
12. =
1 + cot2 A cos2 A
1 + tan2 A sec2 A
=
1 + cot2 A csc2 A
1
cos2 A
= 1
sen2 A
2
sen A
= 
cos2 A
secA − tanA
13. = 1 − 2secAtanA + 2tan2 A
secA + tanA
secA − tanA secA − tanA secA − tanA
= ·
secA + tanA secA + tanA secA − tanA
(secA − tanA)2
=
sec2 A − tan2 A
sec2 A − 2secAtanA + tan2 A
=
1
= 1 + tan A − 2secAtanA + tan2 A
2

= 1 − 2secAtanA + 2tan2 A 

4
tanA cotA
14. + = secAcscA + 1
1 − cotA 1 − tanA
senA cosA
tanA cotA cosA senA
+ = cosA
+
1 − cotA 1 − tanA 1 − senA 1 − senA
cosA
senA cosA
cosA senA
= senA−cosA
+ cosA−senA
senA cosA
sen2 A cos2 A
= +
cosA(senA − cosA) senA(cosA − senA)
sen2 A cos2 A
= −
cosA(senA − cosA) senA(senA − cosA)
sen3 A − cos3 A
=
cosAsenA(senA − cosA)
((( 2 2
(((−(cosA)(sen A + senAcosA + cos A)
(senA
= (
((((
cosAsenA( (((− cosA)
(senA
1 + senAcosA
=
cosAsenA
1
= +1
cosAsenA
1 1
= · +1
cosA senA
= secAcscA + 1 

cosA senA
15. + = senA + cosA
1 − tanA 1 − cotA
cosA senA cosA senA
+ = senA
+ cosA
1 − tanA 1 − cotA 1 − cosA 1 − senA
cosA senA
= cosA−senA + senA−cosA
cosA senA
cos2 A sen2 A
= +
cosa − senA senA − cosA
cos2 A sen2 A
= −
cosa − senA cosA − senA
cos2 A − sen2 A
=
cosA − senA
(cosA (((
−(senA)(cosA + senA)
(((
= (
(
((− senA
cosA ( ( (
(
= cosA + senA 

5
16. (senA + cosA)(cotA + tanA) = secA + cscA
 
cosA senA
(senA + cosA)(cotA + tanA) = (senA + cosA) +
senA cosA
 2
cos A + sen2 A

= (senA + cosA)
senAcosA
 
1
= (senA + cosA)
senAcosA
senA + cosA
=
senAcosA
senA
  cosA
 
= +
senAcosA
  senAcosA

1 1
= +
cosA senA
= secA + cscA 

## sec4 A − sec2 A = sec2 A(sec2 A − 1)

= sec2 A · tan2 A
= (1 + tan2 A)tan2 A
= tan2 A + tan4 A 

## cot4 A + cot2 A = cot2 A(cot2 A + 1)

= cot2 A · csc2 A
= (csc2 A − 1)csc2 A
= csc4 A − csc2 A 

19. csc2 A − 1 = cosAcscA
√ √
csc2 A − 1 = cot2 A
= |cotA|
|cosA|
=
|senA|
cosA
= Si senA · cosA > 0
senA
1
= cosA ·
senA
= cosAcscA 

6
20. sec2 Acsc2 A = tan2 A + cot2 A + 2

## tan2 A + cot2 A + 2 = 1 + tan2 A + 1 + cot2 A

= sec2 A + csc2 A
1 1
= +
cos2 A sen2 A
sen2 A + cos2 A
=
cos2 Asen2 A
1
=
cos Asen2 A
2
1 1
= ·
cos A sen2 A
2

= sec2 Acsc2 A 

## 21. tan2 A − sen2 A = sen4 Asec2 A

sen2 A
tan2 A − sen2 A = − sen2 A
cos2 A  
2 1
= sen A −1
cos2 A
= sen2 A sec2 A − 1
 

= sen2 Atan2 A
sen2 A
= sen2 A
cos2 A
4
sen A
=
cos2 A
= sen4 Asec2 A 

## B = (1 + cotA − cscA)(1 + tanA + secA)

| {z } −cscA − cscAtanA
= 1 + tanA + secA + cotA + 1 + cotAsecA | {z } −cscAsecA
cscA secA
= 1 + tanA + 
secA
 + cotA + 1 +   − 
cscA  − 
cscA  − cscAsecA
secA
= 2 + tanA + cotA − cscAsecA
senA cosA 1
= 2+ + −
cosA senA senAcosA
sen2 A + cos2 A − 1
= 2+
senAcosA
0
= 2+
senAcosA
= 2 

7
1 1 1 1
23. − = −
cscA − cotA senA senA cscA + cotA

MIEMBRO IZQUIERDO:

1 1 1 1
− = 1 cosA

cscA − cotA senA senA
− senA
senA
1 1
= 1−cosA

senA
senA
senA 1
= −
1 − cosA senA
senA 1 + cosA 1
= · −
1 − cosA 1 + cosA senA
senA(1 + cosA) 1
= 2

1 − cos A senA
senA(1
  + cosA) 1
= −
sen2 A senA
1 + cosA − 1
=
senA
cosA
=
senA
= cotA

MIEMBRO DERECHO:

1 1 1 1
− = − 1 cosA
senA cscA + cotA senA senA
+ senA
1 1
= − 1+cosA
senA senA
1 senA
= −
senA 1 + cosA
1 senA 1 − cosA
= − ·
senA 1 + cosA 1 − cosA
1 senA(1 − cosA)
= −
senA 1 − cos2 A
1 senA(1
 
− cosA)
= −
senA sen2 A
1 − 1 + cosA
=
senA
cosA
=
senA
= cotA

8
cotAcosA cotA − cosA
24. =
cotA + cosA cotAcosA
cosA
cotAcosA senA
cosA
= cosA
cotA + cosA senA
+ cosA
cos2 A
senA


= 
cosA+senAcosA
senA
 

2
cos A
=
cosA + senAcosA
cos2 A
=
cosA(1
  + senA)
cosA 1 − senA
= ·
1 + senA 1 − senA
cosA(1 − senA)
=
1 − sen2 A
 − senA)
cosA(1

=
cos2 A
1 − senA cotA
= ·
cosA cotA
cotA − cosA
= 
cosAcotA
cotA + tanB
25. = cotAtanB
cotB + tanA
cotB + tanA
cotAtanB = cotAtanB ·
cotB + tanA
cotAtanB cotB + cotAtanB
   
tanA

=
cotB + tanA
cotA + tanB
= 
cotB + tanA

9
1 − cos2 Asen2 A
 
1 1 2 2
26. B= + cos Asen A =
sec2 A − cos2 A csc2 A − sen2 A 2 + cos2 Asen2 A
 
1 1
B = + cos2 Asen2 A
sec2 A − cos2 A csc2 A − sen2 A
cos2 Asen2 A cos2 Asen2 A
= +
sec2 A − cos2 A csc2 A − sen2 A
cos2 Asen2 A cos2 A cos2 Asen2 A sen2 A
= · + ·
sec2 A − cos2 A cos2 A csc2 A − sen2 A sen2 A
cos4 Asen2 A cos2 Asen4 A
= +
1 − cos4 A 1 − sen4 A
4 2
cos Asen A cos2 Asen4 A
= +
(1 − cos2 A)(1 + cos2 A) (1 − sen2 A)(1 + sen2 A)
cos4 A 2
sen A 2
cos Asen4 A
 

= 2
+ 2
sen A(1 + cos2 A)  cos A(1 + sen2 A)
 

4 4
cos A sen A
= +
1 + cos A 1 + sen2 A
2

## cos4 A(1 + sen2 A) + sen4 A(1 + cos2 A)

=
(1 + cos2 A)(1 + sen2 A)
cos4 A + cos4 Asen2 A + sen4 A + sen4 Acos2 A
=
1 + sen2 A + cos2 A + cos2 Asen2 A
(cos A + sen2 A)2 − 2cos2 Asen2 A + sen2 Acos2 A(cos2 A + sen2 A)
2
=
2 + cos2 Asen2 A
1 − 2cos2 Asen2 A + sen2 Acos2 A · 1
=
2 + cos2 Asen2 A
1 − cos Asen2 A
2
= 
2 + cos2 Asen2 A

## sen8 A − cos8 A = (sen4 A + cos4 A)(sen4 A − cos4 A)

= (sen4 A + cos4 A)(sen2 A − cos2 A)(sen2 A + cos2 A)
= ((sen2 A + cos2 A)2 − 2sen2 Acos2 A) · (sen2 A − cos2 A) · 1
= (1 − 2sen2 Acos2 A)(sen2 A − cos2 A) 

cosAcscA − senAsecA
28. = cscA − secA
cosA + secA
cosA + senA
cscA − secA = (cscA − secA) ·
cosA + senA
(cscA − secA)(cosA + senA)
=
cosA + senA
cscAcosA + 1 − 1 − secAsenA
=
cosA + senA
cscAcosA − secAsenA
= 
cosA + senA

10
tanA + secA − 1 1 + senA
29. =
tanA − secA + 1 cosA
tanA + secA − 1 tanA + secA − 1 cosA
= ·
tanA − secA + 1 tanA − secA + 1 cosA
senA + 1 − cosA
=
senA − 1 + cosA
(senA − cosA) + 1 (senA + cosA) + 1
= ·
(senA + cosA) − 1 (senA + cosA) + 1
sen2 A + ( + senA − ( − cos2 A − cosA + senA + cosA + 1
( (
senAcosA senAcosA
( (
((( (((
=
(senA + cosA)1 − 1
sen2 A + 2senA − cos2 A + 1
=
sen2 A + 2senAcosA + cos2 A − 1
sen2 A + 2senA + cos2 − 2cos2 A + 1
=
2senAcosA
2 + 2senA − 2cos2 A
=
2senAcosA
1 + senA − cos2 A
=
senAcosA
sen2 A +  2
cos A + senA −  2
cos A
 
=
senAcosA
sen2 A + senA
=
senAcosA
senA(senA
  + 1)
=
senAcosA
  
senA + 1
= 
cosA

## C = (tanA + cscB)2 − (cotB − secA)2

= tan2 A + 2tanAcscB + csc2 B − cot2 B + 2cotBsecA − sec2 A
=  2
sec A −
 2
csc B + 2tanAcscB + 
 2
csc B + 2cotBsecA − 
 2
sec A


= 2(tanAcscB + cotBsecA)
  
tanAcscB 
 cotBsecA

= 2tanAcotB +
tanAcotB
  tanA cotB

= 2tanAcotB (cscBtanB + secAcotA)
 
1 senB
 1  cosA

= 2tanAcotB + 
senB
  cosB cosA senA

1 1
= 2tanAcotB( + )
cosB senA
= 2tanAcotB(secB + cscA) 

11
31. 2sec2 A − sec4 A − 2csc2 A + csc4 A = cot4 A − tan4 A

2sec2 A − sec4 A − 2csc2 A + csc4 A = sec2 A + sec2 A − sec4 A − csc2 A − csc2 A + csc4 A
= sec2 A + sec2 A(1 − sec2 A) − csc2 A − csc2 A(1 − csc2 A)
= sec2 A + sec2 A · −tan2 A + −csc2 A − csc2 A · −cot2 A
= tan2 A − cot2 A − sec2 Atan2 A + csc2 Acot2 A
= tan2 A − sec2 Atan2 A + csc2 Acot2 A − cot2 A
= tan2 A(1 − sec2 A) + cot2 A(csc2 A − 1)
= tan2 A · −tan2 A + cot2 A · cot2 A
= −tan4 A + cot4 A
= cot4 A − tan4 A 

1 − senA
32. = 1 + 2tanA(tanA − secA)
1 + senA
1 − senA 1 − senA 1 − senA
= ·
1 + senA 1 + senA 1 − senA
(1 − senA)2
=
1 − sen2 A
1 − 2senA + sen2 A
=
cos2 A
1 senA sen2 A
= − +
cos2 A cos2 A cos2 A
= sec2 A − 2tanAsecA + tan2 A
= 1 + tan2 A − 2tanAsecA + tan2 A
= 1 + 2tan2 A − 2tanAsecA
= 1 + 2tanA(tanA − secA) 

secA cscA
33. B = (1 + cotA + tanA)(senA − cosA) = −
csc A sec2 A
2

## B = (1 + cotA + tanA)(senA − cosA)

= senA − cosA + cotAsenA − cotAcosA + tanAsenA − tanAcosA
cosA cosA senA senA
= senA − cosA +  ·   −
senA · cosA + · senA −  · 
cosA

senA
 senA cosA cosA

2 2
 −   − cos A sen A
= 
senA cosA
 + 
cosA + −senA

senA cosA
sen2 A cos2 A
= −
cosA senA
secA cscA
= − 
csc2 A sec2 A

12